Perbedaan Keterampilan Berpikir Kritis dan Keterampilan Argumentasi Melalui Pembelajaran Argument Driven Inquiry dan Discovery Learning - Fasira, Era; Daud, Firdaus; Azis, Andi Asmawati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to analyze the differences in critical thinking skills and argumentation skills through the application of argument driven inquiry and discovery learning models in biotechnology material. The research method is a quasi-experiment with a quantitative approach using a pretest posttest control group design. The research population was all class X MIA consisting of 3 classes. The research samples were X MIA 2 as experimental class 1 and X MIA 1 as experimental class 2 selected using random sampling techniques. Data collection used critical thinking skills test instruments and argumentation skills tests in the form of 10 essay questions. The posttest t-test results for critical thinking skills obtained a value of 0.01, which is smaller than 0.05, thus showing that there are differences in critical thinking skills in classes that use argument driven inquiry and discovery learning models on biotechnology material. The results of the t-test posttest on argumentation skills obtained a value of 0.00, which is smaller than 0.05, thus indicating that there are differences in argumentation skills in classes that use argument driven inquiry and discovery learning models.